2022
DOI: 10.1038/s41598-022-19438-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation of myokines that enhance osteoclast differentiation and activity

Abstract: Osteoporosis and sarcopenia are maladies of aging that negatively affect more women than men. In recent years, it has become apparent that bone and muscle are coupled not only mechanically as muscle pulls on bone, but also at a higher level with myokines, biochemical and molecular signaling occurring between cells of the two tissues. However, how estrogen deficiency in females impacts the chemical crosstalk between bone and muscle cells is not understood. We hypothesize that changes in estrogen signaling alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
6
0
2
Order By: Relevance
“…This ultrastructural injury was also in accord with the top enriched GO_BP terms. These findings confirmed that estrogen insufficiency impaired the structure and function of skeletal muscle, in agreement with similar researches ( 8 , 45 , 46 ). Moreover, decreased expression of ER-β showed evidence for the impaired estrogen-ER signaling, and we subsequently obtained the corresponding results of down-regulated expression of ESRRG (Estrogen-related Receptor Gamma) (log2FC -1.046)) and the estrogen signaling pathway, which possibly accounted for the consequent histologic findings of myofibers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This ultrastructural injury was also in accord with the top enriched GO_BP terms. These findings confirmed that estrogen insufficiency impaired the structure and function of skeletal muscle, in agreement with similar researches ( 8 , 45 , 46 ). Moreover, decreased expression of ER-β showed evidence for the impaired estrogen-ER signaling, and we subsequently obtained the corresponding results of down-regulated expression of ESRRG (Estrogen-related Receptor Gamma) (log2FC -1.046)) and the estrogen signaling pathway, which possibly accounted for the consequent histologic findings of myofibers.…”
Section: Discussionsupporting
confidence: 92%
“…The hormone-related sarcopenia shares similar characters with the age-related sarcopenia. Nevertheless, postmenopausal women take more risks of musculoskeletal disorders than men of the same age ( 46 48 ). Current clinical treatments for sarcopenia are limited to exercise and diet intervention and quite deficient in medicine ( 34 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal osteoporosis due to decreased estrogen levels and ovariectomized models show the characteristics of reduced estrogen levels ( 76 ). A recent study has demonstrated that estrogen signaling regulates expression and secretion of myokines that modulate osteoclast differentiation and activity.…”
Section: Mechanisms Of Exercise On Bone Healthmentioning
confidence: 99%
“…A recent study has demonstrated that estrogen signaling regulates expression and secretion of myokines that modulate osteoclast differentiation and activity. The authors used conditioned media that were collected from ovariectomized and skeletal muscle deficient in estrogen receptor α expression mice, with cytokine array, and found that estrogen deficiency altered myokines levels ( 76 ).…”
Section: Mechanisms Of Exercise On Bone Healthmentioning
confidence: 99%
“…Neighboring muscle interacts not only mechanically with bone but also through biochemical pathways and mediators 9–12 . For example, paracrine signals known as myokines (cytokines produced by muscle) and osteokines (cytokines produced by bone) mediate the crosstalk between these two tissues 9 .…”
Section: Introductionmentioning
confidence: 99%